Cytokines and Regulating Epithelial Cell Division - Abdullah Marzoog, Basheer (Current Drug Targets, 2024)
Physiologically, cytokines play an extremely important role in maintaining cellular and subcellular homeostasis, as they interact almost with every cell in the organism. Therefore, cytokines play a significantly critical role in the field of pathogenic pharmacological therapy of different types of pathologies. Cytokine is a large family containing many subfamilies and can be evaluated into groups according to their action on epithelial cell proliferation; stimulatory include transforming growth factor-α (TGF-α), Interlukine-22 (IL-22), IL-13, IL-6, IL-1RA and IL-17 and inhibitory include IL-1α, interferon type I (IFN type I), and TGF-β. The balance between stimulatory and inhibitory cytokines is essential for maintaining normal epithelial cell turnover and tissue homeostasis. Dysregulation of cytokine production can contribute to various pathological conditions, including inflammatory disorders, tissue damage, and cancer. Several cytokines have shown the ability to affect programmed cell death (apoptosis) and the capability to suppress non-purpose cell proliferation. Clinically, understanding the role of cytokines' role in epithelial tissue is crucial for evaluating a novel therapeutic target that can be of use as a new tactic in the management of carcinomas and tissue healing capacity. The review provides a comprehensive and up-to-date synthesis of current knowledge regarding the multifaceted effects of cytokines on epithelial cell proliferation, with a particular emphasis on the intestinal epithelium. Also, the paper will highlight the diverse signaling pathways activated by cytokines and their downstream consequences on epithelial cell division. It will also explore the potential therapeutic implications of targeting cytokine- epithelial cell interactions in the context of various diseases.
Keywords: differentiation